Renal disease in systemic lupus erythematosus: correlation of morphology with clinical course - Van Diggelen, Nicholas Tromp (Division of Anatomical Pathology, 2017)
Patients were selected for the study on the basis of 1: A diagnosis of systemic Lupus Erythematosus according to the 1982 revised American Rheumatology Association criteria47 and 2: An adequate biopsy defined as containing at least six glomeruli. Patients were biopsied at Groote Schuur Hospital during the period 1978 to 1988 and the indications for renal biopsy were clinical based on laboratory results of renal function. Patients were followed between 1 and 120 months with a mean observation period of 34 months. The clinical records were scrutinised and the following pa·rameters were noted at the time of biopsy: age, sex, race, time from diagnosis to biopsy, serum urea, creatinine, creatinine clearence and urinary 24 hour protein. Using the latest serum urea, creatinine, creatinine clearence and / or 24 hour urinary protein where available, outcome was graded as: 1: An improvement in renal function 2: A stable renal function 3: Deterioration in renal function 4: Patient on dialysis 5: Death due to disease.